Km-scale climate simulations over Madeira and Canary Islands under present and future conditions: a model intercomparison study - Adinolfi, Marianna; Loprieno, Leo Luca; Demory, Marie-Estelle; id_orcid:0 000-0002-5764-3248; Zeman, Christian; Schär, Christoph; id_orcid:0 000-0002-4171-1613 (Springer, 2025)
This study seeks to explore two new km-scale regional climate simulations prepared through the European Climate Prediction project over the Madeira and Canary islands, which are Portuguese and Spanish archipelagos located in the North Atlantic, off the African coast. The simulations are based on two models using different modelling approaches: COSMO-CLM with a three-step nesting at 50, 25 and 3 km grid spacing using a time-slice approach driven by a global climate model, and COSMO-crCLIM with a two-step nesting at 12 and 1 km grid spacing using the pseudo-global warming approach, where the current-day simulations are driven by ERA-Interim reanalysis. Although the modelling approaches are different, several findings are highlighted: (1) the use of km-scale simulation is essential to properly represent temperature and precipitation mean and extremes over small islands that are characterized by complex topography; (2) the projected changes in temperature and precipitation mean and extremes are qualitatively similar in all seasons except autumn; (3) the differences in the autumn projections are shown to be due to the large-scale driving conditions. Small islands, such as the Canary and Madeira ones, are often neglected by large modelling initiatives, so the presented simulations contribute to filling this gap for local policy makers, stakeholders and climate services. The encouraging results highlight the need for further coordinated km-scale projections. ISSN:0930-7575 ISSN:1432-0894